DEVELOPMENT AND VALIDATION OF SCHADENFREUDE SCALE - Dr. Rubina Hanif (Journal of Peace, Development and Communication, 2021)
The present study aimed at examining the feelings of schadenfreude among adolescents. The study based on the development and validation of schadenfreude scale. Schadenfreude is a sort of pleasure which is experienced on someone else misfortune. The study comprised of two phases: phase-I was consisted on the development of the scale whereas phase-II was based on the establishment of psychometric properties of the scale. In phase-I item pool was generated on the basis on literature as well as content analysis of the information obtained through focus groups and it was finalized through committee approach. In phase-II psychometric properties of the scale were established by conducting 1) Exploratory Factor Analysis (N=330), 2) descriptive statistics, alpha reliabilities, correlations, and 3) Confirmatory Factor Analysis (N=320). After EFA and CFA, the final scale comprised of 28 statements and six domains. The domains included Rivalry/Conflict (8 statements), Negative Attitude (3 statements), Injustice (4 statements), Deservingness (3 statements), Comparison (5 statements), and Perceived Helplessness (5 statements). The resultant Schadenfreude Scale is a valid and reliable measure to investigate schadenfreude among adolescents. Keywords: Schadenfreude, EFA, CFA